Legal Strategy for Exposing Covert Cartel Agreements Through Indirect Evidence and Leniency Programs - Kagramanto, Lucianus Budi; Anggriawan, Teddy Prima (Universitas Airlangga, 2025)
Indirect evidence is a form of indirect proof provided to seek material truth in the context of competition law enforcement. The leniency program is part of the final proofing process after law enforcers have utilized both direct and indirect evidence. The efficacy of the leniency program will eliminate cartel behaviors that greatly disrupt consumer welfare. This program is one of the roles of law in Indonesia, which is to maintain and regulate the economic activities among business actors so then these activities are orderly and balanced. The leniency program itself is a new substantive system included in the Draft Bill on the Prohibition of Monopolistic Practices and Unfair Business Competition in the amendment to Law No. 5/1999. The urgency of this amendment is also reflected in the 2025-2029 RPJMN, particularly in strengthening the economic transformation foundation through legal certainty and strengthening business competition, including competition institutions. The goal to be achieved is to eradicate cartel actors who violate the established rules in accordance with existing regulations. The program will have a positive impact on the sustainability and welfare of consumers in Indonesia regarding market production pricing. The research method used is normative legal research with a conceptual approach that is descriptive in nature. This research is highly likely to be implemented in Indonesia; both matters can be carried out by establishing a comprehensive Draft Law (RUU) on the Prohibition of Monopoly Practices and Unfair Business Competition.